1999
DOI: 10.1104/pp.119.3.885
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Water Permeability of Isolated Protoplasts. Modifications during Development1

Abstract: A transference chamber was developed to measure the osmotic water permeability coefficient (P os ) in protoplasts 40 to 120 m in diameter. The protoplast was held by a micropipette and submitted to a steep osmotic gradient created in the transference chamber. P os was derived from the changes in protoplast dimensions, as measured using a light microscope. Permeabilities were in the range 1 to 1000 m s ؊1 for the various types of protoplasts tested. The precision for P os was <40%, and within this limit, no asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 37 publications
8
81
1
Order By: Relevance
“…n et al, 1997). Other recent reports showed that rape (Brassica napus) protoplasts, fixed through suction applied to a glass pipette, had a linear variation for c. 10 s (Ramahaleo et al, 1999). In our experiments the mixing time was c. 3 s, therefore we still were in the linear part of the curve as shown in Fig.…”
Section: mentioning
confidence: 47%
See 1 more Smart Citation
“…n et al, 1997). Other recent reports showed that rape (Brassica napus) protoplasts, fixed through suction applied to a glass pipette, had a linear variation for c. 10 s (Ramahaleo et al, 1999). In our experiments the mixing time was c. 3 s, therefore we still were in the linear part of the curve as shown in Fig.…”
Section: mentioning
confidence: 47%
“…The fact that a strong decrease in P f was observed in NaCltreated protoplasts compared to controls, and that there was practically no Hg inhibition, led us to consider that aquaporins were inactivated. Ramahaleo et al (1999) suggested that mercury could be damaging the protoplasts in their experiments, since the reduction in P f could be interpreted as the induction of leakage of osmoticum across the membrane. However, in our experiments the fact that Hg was present in the protoplast media for only 2 min and was then removed could explain why damage to the cells was greatly reduced.…”
Section: mentioning
confidence: 99%
“…Isolated protoplasts were resuspended in a storing solution (mannitol, 500 mmol/kg; Ca(No 3 ) 2 , 1 mM; bovine serum albumin, 0.05% w/v; MES, 5 mM, buffered with Tris to pH 5.5), and P os was measured at room temperature according to a technique previously described (Ramahaleo et al, 1999); the value of P os was deduced from the initial rate of swelling of the protoplast, when transferred from the stock solution to a solution with lower osmoticum (mannitol, 100-300 mmol/kg; Ca(No 3 ) 2 , 1 mM; bovine serum albumin, 0.05% w/v; MES, 5 mM, buffered with Tris to pH 5.5).…”
Section: P Os Measurementsmentioning
confidence: 99%
“…6), as previously described (Ramahaleo et al, 1999). The data are presented on a logarithmic scale because of the wide range of P os values obtained.…”
mentioning
confidence: 99%
“…Two different methods were previously described based on this approach, both based on an instantaneous exchange of solutions. The first one consists of immobilizing the protoplast with a suction micropipette and switching the solution flow 5 and the second one of transferring the protoplast from one solution to another using a micropipette 6 . These micropipette suction and micropipette transferring methods, which allow image acquisition at the very start of the fast solution exchange (to capture the early linear phase of volume change), likely involve a physical stress to protoplasts and require specialized equipment and expert micromanipulation.…”
Section: Introductionmentioning
confidence: 99%